Tamanho de amostra para caracteres morfológicos e produtivos de centeio - Bandeira, Cirineu Tolfo (2017)
The objective of this study was to determine the sample size for morphological and productive characteristics of the rye crop, as a function of sowing times and cultivars. Uniformity trials with two rye cultivars and five sowing seasons were conducted at the Plant Science Department of the Federal University of Santa Maria, in the agricultural year of 2016. In each trial, the weekly plant height, number of leaves and number of stems in 100 previously marked plants (Chapter 1). When these plants were in the flowering stage, they were collected and 11 characters were evaluated (Chapter 2). At the harvesting point, 90 plants were randomly collected in the third and fourth sowing seasons of the cultivars Temprano and BRS Progresso, respectively, and 100 plants in the other seasons. In these plants were measured 17 characters (Chapter 3). In the characters evaluated weekly, the F test was applied to test the hypothesis of homogeneity of variances and the Student t test to test the hypothesis of equality of means between characters, between cultivars and between sowing and evaluation times. The sample size of each character was calculated for distinct mean estimation errors. In the characters evaluated for the flowering of the culture, the descriptive statistics were calculated and the sample size was determined for the mean estimation at precision levels (95% confidence intervals (AIC95%) of 5, 10, ..., 35 % of the average) by resampling, with replacement. For the characters evaluated at the point of collection, the descriptive statistics were calculated and the sample size was determined for the mean and coefficient of variation estimation at precision levels (AIC95% of 5, 10, 15, 20, 25 and 30% of the mean and coefficient of variation) by resampling with replacement. There is variability in the estimation of sample size among the evaluated characters, cultivars, sowing times and evaluation. In the weekly evaluated traits, 25, 61 and 83 plants are required for BRS Progresso cultivar and 60, 99 and 103 plants in the cultivar Temprano, for the estimation of the mean plant height, leaf number and number of stems, respectively , with maximum error of estimation of 15% (Chapter 1). At flowering, the measurements of 425, 276, 189 and 138 plants in the cultivar BRS Progresso and 642, 413, 285 and 211 plants in the cultivar Temprano were sufficient for the estimation of the mean with AIC95% of 20 , 25, 30 and 35%, respectively, for all characters and sowing times (Chapter 2). For the characters evaluated at the sampling point, there is variability in the sample size for the estimation of the mean and coefficient of variation for productive characters, cultivars and sowing times, in addition to the sample size being larger for the estimation of the coefficient of variation of the than for the mean estimation (Chapter 3).